Post-Harvest Eucalyptus Residue Removal Reduces Soil Aggregation and Biological Activities in Central-West Brazil - Sena, Karla Nascimento [UNESP]; Boni, Thaís Soto [UNESP]; Maltoni, Kátia Luciene [UNESP]; Cassiolato, Ana Maria Rodrigues [UNESP]; Pujol Pereira, Engil Isadora (MDPI, 2023)
Tree residue removal from Eucalyptus plantations after timber harvest can reduce soil functioning by reducing the organic matter input. To assess the effects of residue management systems (RMS) on soil aggregation, carbon (C) and nitrogen (N) content, and biological activities, a field trial was conducted in a commercial Eucalyptus plantation (loamy sand soil) in Mato Grosso do Sul, Brazil. The study assessed three RMS: cut-to-length (CTL), tree-length (TL), and bare litter (BL), respectively. After 21 months, undisturbed soil samples were collected and physically isolated into three aggregate-size fractions: large macroaggregates (LM), medium macroaggregates (SM), and microaggregates (MI). Results showed that these soils are mostly composed of LM (54%), and that removing harvest residues from the growing site included total organic carbon (TOC) by 28%, microbial biomass-C by 20%, fluorescein diacetate hydrolysis by 17%, and β-glucosidase activity by 26%, when compared to CTL. TL outperformed CTL for the proportion of LM and LM-associated TOC. Across fractions, a higher microbial quotient was observed in SM and MI fractions, suggesting that the TOC has higher stability inside the LM. This study suggests that leaving harvest residues on the soil should be recommended for Eucalyptus plantations, especially in low-fertility sandy soils, as it helps in maintaining the soil structure and biological activities critical for soil health and ecosystem function.
Keywords: aggregate stability; sandy soils; soil enzyme activity; soil health